2014
DOI: 10.1097/iae.0b013e3182993df1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reticular Pseudodrusen on Macular Function

Abstract: Eyes with reticular pseudodrusen present a greater extent of reduced sensitivity than eyes with typical drusen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
57
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 27 publications
6
57
1
Order By: Relevance
“…29,30 Several reports have shown that retinal sensitivity is reduced in eyes with pseudodrusen. [31][32][33][34] Consistent with these reports, the mean retinal sensitivity of the area without photoreceptor damage and RPE loss was lower in eyes with pseudodrusen compared with eyes without them. All these results indicate that pseudodrusen themselves may cause retinal sensitivity reduction.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 88%
“…29,30 Several reports have shown that retinal sensitivity is reduced in eyes with pseudodrusen. [31][32][33][34] Consistent with these reports, the mean retinal sensitivity of the area without photoreceptor damage and RPE loss was lower in eyes with pseudodrusen compared with eyes without them. All these results indicate that pseudodrusen themselves may cause retinal sensitivity reduction.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 88%
“…34 Impaired nutrient exchange between photoreceptors and choriocapillaris due to blocked access by pseudodrusen material accumulation has been suggested as one of the possible mechanisms underlying this relationship. 33 We postulate that this blocking effect is greater in ribbon pseudodrusen than in dot pseudodrusen because ribbon pseudodrusen is usually larger and has a more densely packed appearance than dot pseudodrusen. In this study, eyes with ribbon pseudodrusen exhibited relatively thin choroids than those with dot pseudodrusen only.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, RPD are known to affect photoreceptor function, in particular function of rods [8][9][10][11][12][13][14][15]. Together with a higher RPD prevalence in predominantly rod-rich macular regions and a spatial correlation of RPD and damaged rod photoreceptors, it was hypothesized that a pathophysiologic relation may exist between RPD and rods [16].…”
Section: Introductionmentioning
confidence: 97%